La comunidad cubanoamericana y la política de Estados Unidos hacia Cuba: Historia y presente - Dalia González Delgado (Études Caribéennes)
This article examines the evolution of the Cuban-American community, taking into account the socio-demographic transformations, as well as the levels of insertion within the United States political system. The main goal is to explain its possible influence in the policy making process towards Cuba.